A Phos‐tag‐based micropipette‐tip method for rapid and selective enrichment of phosphopeptides. Issue 19 (10th July 2017) - Yuan, Elena Tianfei; Ino, Yoko; Kawaguchi, Maho; Kimura, Yayoi; Hirano, Hisashi; Kinoshita‐Kikuta, Emiko; Kinoshita, Eiji; Koike, Tohru
Abstract: Phosphorylated peptides are attractive targets in the study of the phosphoproteome. Here, we introduce a simple and convenient micropipette‐tip method for the separation of phosphorylated and nonphosphorylated peptides by using a phosphate‐binding zinc(II) complex of 1, 3‐bis(pyridin‐2‐ylmethylamino)propan‐2‐olate (Phos‐tag). A 200‐μL micropipette tip containing 10 μL of swollen agarose beads functionalized with Phos‐tag moieties was prepared. All steps in the phosphate‐affinity separation (binding, washing, and elution) were conducted by using aqueous buffers at neutral pH values. The entire separation protocol required less than 30 min per sample. By means of three independent separation experiments, followed by mass spectrometric (MS) analyses, we identified 1, 649 non‐redundant phosphopeptides from the lysates of human embryonic kidney cells (the peptides sample derived from 25 μg proteins per an MS analysis). The average ratio of identified phosphopeptides to total peptides in the respective experiments was >90%, showing a high selectivity. Furthermore, the high correlation between the triplicate analyses was confirmed by scatter plots based on the normalized abundance of each peptide, as calculated by a label‐free peptide relative quantification analysis in Progenesis QI. This micropipette‐tip method would be thus used preferentially as an alternative to existing tools for the reliable enrichment of phosphopeptides.